2019
DOI: 10.1186/s13068-019-1561-1
|View full text |Cite
|
Sign up to set email alerts
|

Effective continuous acetone–butanol–ethanol production with full utilization of cassava by immobilized symbiotic TSH06

Abstract: Background Butanol production by fermentation has recently attracted increasingly more attention because of its mild reaction conditions and environmentally friendly properties. However, traditional feedstocks, such as corn, are food supplies for human beings and are expensive and not suitable for butanol production at a large scale. In this study, acetone, butanol, and ethanol (ABE) fermentation with non-pretreated cassava using a symbiotic TSH06 was investigated. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 33 publications
1
5
0
Order By: Relevance
“…In the previous study, it was found that TSH06 has the ability to directly produce butanol from cassava flour, without the pretreatment enzymatic hydrolysis or gelatinization [8]. Considering that the concentration of substrate can affect the fermentation performance, in this work, different concentrations of cassava media were used for butanol fermentation to observe the butanol synthesis by TSH06.…”
Section: Effect Of Cassava Concentrations On Butanol Synthesis By Tsh06mentioning
confidence: 99%
See 2 more Smart Citations
“…In the previous study, it was found that TSH06 has the ability to directly produce butanol from cassava flour, without the pretreatment enzymatic hydrolysis or gelatinization [8]. Considering that the concentration of substrate can affect the fermentation performance, in this work, different concentrations of cassava media were used for butanol fermentation to observe the butanol synthesis by TSH06.…”
Section: Effect Of Cassava Concentrations On Butanol Synthesis By Tsh06mentioning
confidence: 99%
“…In the previous study, it was found that continuous fermentation reached a steady state within 24-36 h of initiation. Therefore, the gas-stripping device was activated after 36 h of continuous fermentation [8]. After 36 h of continuous fermentation, the concentration of butanol was 8.8 g/L.…”
Section: Single-stage Continuous Fermentation Coupled With Online Gas...mentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, use of butanol as a biofuel has remarkable advantages over ethanol in terms of higher energy, low volatility and can be mixed or completely replace current fuel systems (Green, 2011). Cassava flour, gelatinized starch and starch hydrolysate have been fermented to produce butanol (Lin et al, 2019; T. Li et al, 2015; Thang et al, 2010). The fermentation of cassava starch hydrolysate produced the highest butanol concentration of 25.7 g/L (Lépiz‐Aguilar et al, 2013).…”
Section: Cassava As a Bioenergy Cropmentioning
confidence: 99%
“…This leads to a partial loss of soluble carbohydrates from hemicelluloses, an increase in required process steps and increased water and chemical consumption. Another promising approach is to search for or construct more tolerant strains [ 33 35 ]; the use of multispecies consortia [ 36 ] and strains having inherent enhanced detoxification capacity [ 14 ].…”
Section: Introductionmentioning
confidence: 99%